MAXIMUM POWER POINT TRACKING (MPPT) PADA SOLAR PANEL DENGAN SISTEM TRACKING - Niken Ananda; M.Isra' Nurcahya Kuncoro; I Made Andik Setiawan; Surojo (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Solar panels are a tool for reducing the amount of pollution in the atmosphere because they are the most efficient source of energy. Matahari radiation from a solar panel in comparison to the tegangan and arus produced by the solar panel itself. Namun, dalam proses pemakaiannya, sebagian saja yang dimanfaatkan dari sinar matahari, daya yang diserap tidak digunakan sepenuhnya, karena tergantung dari jenis beban yang digunakan. Maximum Power Point Tracking is used on solar panels to optimize daytime performance. Maximum Power Point Tracking adalah sistem elektronis yang mengoperasikan modul solar panel untuk menghasilkan daya yang dapat diproduksi oleh solar panel dengan sistem tracking. In the following project, a manual tracking system is used to adjust the solar panel so that it does not lag behind the time of day with a maximum voltage of 17,42 v, a maximum current of 718,4 mA, and a maximum day of 13662 w. Solar panel 100 wp, buck-boost converter, sensor arus ina 219, sensor tegangan, potensio, lcd i2c, and microcontroller arduino mega 2560 are the components used.